Consideration of Administrative Monetary Penalties in Nuclear Safety and Security - Jelena Vucicevic; Edward Waller (International Journal of Nuclear Security, 2020)
An Administrative Monetary Penalty (AMP) is a penalty imposed by the Canadian Nuclear Safety Commission (CNSC), without court involvement for a violation of a regulatory requirement. An AMP can be applied against any individual or corporation subject to the Nuclear Safety Control Act, which regulates the development, production and use of nuclear energy and the production, possession and use of nuclear and radioactive material. However, AMPs are not the same as criminal offences. They are civil sanctions which try to secure compliance through the application of monetary penalties for non-compliance with regulatory requirements. The AMP program was introduced in 2013 in Canada and to this date over 30 penalties have been issued. In all of these cases, the violations were related to handling and security of radioactive material. Based on these issued penalties investigations were conducted to discover pros and cons of the AMP system and to propose potential improvements for future implementation. This paper also addresses some of the complicated issues of the system, such as the economic aspect of the process, and the subjectivity and relative ease of issuing these penalties. In order to improve nuclear security in Canada, the regulator must be aware of possible violations of the Nuclear Safety Control Act and work on prevention of these violations. It is postulated that current AMP policy may not motivate individuals or corporations to report violations. The paper gives recommendations on modifications which could be implemented to motivate self – identification of violation, and give significant benefit to the AMP system. Other than the issued AMPs, the paper will analyze data obtained through the survey conducted on human readiness to self – identify violations in the nuclear industry under different circumstances. This confirms that the modified AMP policy would improve the body of knowledge and provide significant information on violations of the Nuclear Safety Control Act and improve nuclear security.
Keywords: Administrative Monetary Penalty; nuclear security; nuclear safety; regulations